The Tip of the Hydrophobic Hairpin of Colicin U Is Dispensable for Colicin U Activity but Is Important for Interaction with the Immunity Protein - Pilsl, Holger (American Society for Microbiology, 1998)
The hydrophobic C terminus of pore-forming colicins associates with and inserts into the cytoplasmic membrane and is the target of the respective immunity protein. The hydrophobic region of colicin U of Shigella boydii was mutated to identify determinants responsible for recognition of colicin U by the colicin U immunity protein. Deletion of the tip of the hydrophobic hairpin of colicin U resulted in a fully active colicin that was no longer inactivated by the colicin U immunity protein. Replacement of eight amino acids at the tip of the colicin U hairpin by the corresponding amino acids of the related colicin B resulted in colicin U(575–582ColB), which was inactivated by the colicin U immunity protein to 10% of the level of inactivation of the wild-type colicin U. The colicin B immunity protein inactivated colicin U(575–582ColB) to the same degree. These results indicate that the tip of the hydrophobic hairpin of colicin U and of colicin B mainly determines the interaction with the corresponding immunity proteins and is not required for colicin activity. Comparison of these results with published data suggests that interhelical loops and not membrane helices of pore-forming colicins mainly interact with the cognate immunity proteins and that the loops are located in different regions of the A-type and E1-type colicins. The colicin U immunity protein forms four transmembrane segments in the cytoplasmic membrane, and the N and C termini face the cytoplasm.